A money demand system for M3 in the unified Germany - Helmut Lütkepohl; Jürgen Wolters (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1997)
A small macroeconomicmodel is constructed starting from a German money demand relation for M3 based on quarterly, seasonally unadjusted data for the period from 1976 to 1996. In contrast to previous studies we build a vector error correction model for M3, GNP, an inflation rate and an interest rate spread variable to represent opportunity costs of holding money. Furthermore, import price ination is added as an exogenous variable. The model is used to analyze the relation between money growth and ination by means of an impulse response analysis.
urn:nbn:de:kobv:11-10064688
Keywords: 330